RETRACTED : FACTORIZATION OF THE DEGREE OF SPHENIC POLYNOMES - Beletsky, Anatoly; Kovalchuk, Arsen (Ukrainian Information Security Research Journal, 2022)
RETRACTION NOTICE This article has been retracted by the Editorial Board in accordance with the Journal Retraction Policy. Reason for retraction: the publication does not comply with the current requirements of the legislation of Ukraine regarding the language of scientific publications. The retraction is not related to plagiarism, research misconduct, fabrication, falsification of results or other violations of academic integrity. Editorial Board of the Ukrainian Information Security Research Journal By sphenic polynomials, we mean polynomials formed by the product of three (not necessarily different) irreducible polynomials with a priori unknown degree. The study's main goal is to develop an effective algorithm for factorizing degrees of sphenic polynomials with minimal computational complexity. Different solutions to the problem of factorization degrees of sphenic polynomials depending on the ratio degree of the cycle period of these polynomials consider. The sphenic polynomial cycle period defines as a parameter equal to the number of non-repeating subtractions computed on the linear-logarithmic scale of the group formed by the sphenic polynomial. The proposed algorithm is invariant to the characteristics of the Galois fields generated by the multipliers of sphenic polynomials. Numerous numerical examples confirm the correctness of the results. Directions for further research outlines.